Material and Non-material Motivation Factors - Janjić, Teodora; Micić, Radmila (Economic Outlook, 2024)
This paper presents the level of employee motivation at ABC Proizvod from Užice, as well as the structure of material and non-material motivation factors. The aim of the paper is to discover, based on the opinions of employees at the local company in Užice, whether material or non-material motivation factors are more important to them and to determine the degree of motivation present in the mentioned company. Using survey methods, descriptive statistics and Spearman's correlation coefficient, it has been concluded that employees are motivated to perform their work tasks and are satisfied with their jobs. Among the motivational factors, the employees appreciate increase in salary the most. In terms of material incentives, the company offers salary increases and additional bonuses, while non-material incentives include opportunities for growth and development. To a somewhat lesser extent, a pleasant working atmosphere.